2017
DOI: 10.1128/jvi.01879-16
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Porcine Circovirus Distantly Related to Known Circoviruses Is Associated with Porcine Dermatitis and Nephropathy Syndrome and Reproductive Failure

Abstract: Porcine circovirus-associated disease (PCVAD) is clinically manifested by postweaning multisystemic wasting syndrome (PMWS), respiratory and enteric disease, reproductive failure, and porcine dermatitis and nephropathy syndrome (PDNS). Porcine circovirus 2 (PCV2) is an essential component of PCVAD, although an etiologic role in PDNS is not well established. Here, a novel circovirus, designated porcine circovirus 3 (PCV3), was identified in sows that died acutely with PDNS-like clinical signs. The capsid and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
802
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(844 citation statements)
references
References 69 publications
33
802
0
9
Order By: Relevance
“…It has been suggested that excessive PCV2 antibody titers may trigger the development of PDNS [38]. In addition, other etiological agents such as PRRSV and torque teno virus [39] or PCV3 [40] have also been proposed as triggers or causative agents in PDNS. The PDNS-affected pig in this study had no detectable PCV2 antibody titer at challenge and the titer increased towards a low positive level over the following weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that excessive PCV2 antibody titers may trigger the development of PDNS [38]. In addition, other etiological agents such as PRRSV and torque teno virus [39] or PCV3 [40] have also been proposed as triggers or causative agents in PDNS. The PDNS-affected pig in this study had no detectable PCV2 antibody titer at challenge and the titer increased towards a low positive level over the following weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, three sequences of capsid gene from the United Kingdom and five sequences from the United States detected by this study showed 100% identity to PCV3/KU‐1602 from Korea (Kwon et al . ) and PCV3 29160 from the United States (Palinski et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…We did not compare our method with another important real‐time PCR established by Palinski et al . (). due to technical difficulties in synthesis of their designed probe.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, a new swine circovirus species named PCV‐3 has been described (Palinski et al . ). Its genome includes two major open reading frames (ORFs), ORF1 and ORF2, located in different strands of the viral replicative form, oriented in opposite direction and encoding the replicase (Rep) and capsid (Cap) proteins, respectively (Palinski et al .…”
Section: Introductionmentioning
confidence: 97%
“…PCV‐3 has been reported in North and South America (Palinski et al . ; Tochetto et al . ), Asia (Kwon et al .…”
Section: Introductionmentioning
confidence: 99%